Literasi Membaca: Eksplorasi Potensi Sekolah dalam Mendukung Perkembangan Literasi Anak - Suras, Febriana Ekananda; Pamungkas, Joko; Rolina, Nelva (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
This study identified the problem of low reading literacy skills in early childhood, so the researchers analyzed the potential of schools to support the improvement of reading literacy skills in kindergarten. This analysis aims to measure the extent of the influence of supporting factors owned by schools in improving reading literacy skills. The approach used is quantitative with the type of survey research using a Cross-Sectional research design. This research was conducted by distributing questionnaires online in the form of Google Forms. The research sample taken was 150 children aged 5-6 years from 15 schools in Makassar City using the random sampling method. The reading literacy instrument was developed by researchers using expert testing and empirical testing. The results of the study were analyzed descriptively and correlation tests using Smart PLS 3. Based on the results of this study, it is described that the fulfillment of supporting factors by schools that are not optimal shows a very significant influence on the development of reading literacy. Researchers' findings of reading literacy skills in early childhood show that children's reading literacy understanding is in various categories, namely very less, less and enough and good.